Persepsi Pengguna Jasa KRL Terhadap Rencana Penataan Ulang Rute KRL Jabodetabek - Kuswati, Atik S; Listifadah, Listifadah (Warta Penelitian Perhubungan, 2011)
One impact of the Greater Jakarta development is the encourage people movement and demand for commuter rail. Jabodetabek Commuter train becomes very important role that primarily serves commuter towns or other location that draw large number of commuter who travel on a daily basis. However, unbalancing of capacity and demand of commuter rail will decline index performances. Tire goal of study identify commuter train service regarding implementation of single operation plan. qualitative and quantitative analysis methods are used in this study which identify factors that affect index performance based on the service quality. The analysis result is majority of respondents (69,2 % ) would use the transport services KRL if the single system operation is applied. Seen from the results of a survey that states continue to use the KRL as much as 69.20% on tire grounds tlrere was no other choice. In order to support the smooth operation of the single, an intensive socialization to the public is needs to be done by PT KCJ especially users KRL such as schedule changes, the tariffs, the frequency of KRL, and new routes KRL. Besides changes in the pattern of operation, operator should provide adequate infrastructure capacity so that it can provide comfort to the passengers which the spread of passengers at some stations.Keywords: commuter rail, services, rerouting.